Integrative Medicine as ?Medicine?: A Perspective - Sanchari Mukhopadhyay; Bharath Holla; Hemant Bhargav; Kishore Kumar Ramakrishna; Umesh Chikkanna; Shivarama Varambally; Bangalore N. Gangadhar (Integrative Medicine Reports, 2022)
With the advent and acceptance of biological medicine, now called as modern biomedicine (or allopathy), the older regional medical systems were categorized as complementary and alternative medicine (CAM). Recently, the term CAM has been replaced with ?integrative medicine.? This viewpoint manuscript focuses on the essential connotation of such terms and clarifies the debates on the several confusing terminologies hampering its actual conceptualization and leading to the ?othering? phenomenon in health care approaches. Integrative medicine, in its essence, is a form of holistic and evidence-based health care approach that includes but is not limited to medical treatment. A closer look at the current management protocols of most noncommunicable diseases, such as diabetes mellitus, hypertension, obesity, pain syndromes, and psychiatric illnesses reveals that it incorporates relevant evidence-based management of all health care domains, along with mainstream pharmacologic and surgical treatment options. These management approaches point toward an already existing integration in the mainstream medical practice. Simultaneous management of all the dimensions of health and illness by expanding the current sphere of integration will ultimately result in comprehensive patient care. Therefore, we conclude that integrative medicine is essentially an application of different ?culturally sensitive? health care approaches, optimally tailored to a given patient's needs and difficulties. Efforts are needed at the clinical, research, and administrative levels to reduce the ?othering? phenomenon seen in health care approaches that are often detrimental to efficient patient care. There is a need to promote collaboration between different disciplines and generate evidence base to optimize integrative medical practice further. Establishing interdisciplinary departments of integrative medicine at mainstream medical institutions may be the first step in this direction.